The Influence of Digital Media Usage on Students' Creativity Skills in Creative Dance Arts Through Extracurricular Arts - Kartika Sari, Pratiwi; Nurmiranda, Andivita (Jurnal Seni Tari, 2024)
This research is motivated by the limitations in the dance learning process during the COVID-19 pandemic, extracurricular activities became inactive and constrained the practice of dance in cultural arts and crafts learning itself. The purpose of this study is to determine the effect of using digital media on the creativity of student creation dance at SDN Sudimara 7. The use of digital media in this study is in the form of TikTok. The research method used is a quantitative experimental one-group pretest-posttest design with data analysis techniques using an independent T-test. Sampling itself is done by purposive sampling. The subjects in this study amounted to 24 students with criteria, namely 6th-grade students of SDN Sudimara 7 who participated in dance extracurricular activities, had smartphones, and used the TikTok application. The results of data analysis found that the average score of digital media pretests in the experimental class was 63.54 with an average score of digital media posttests in the experimental class of 75.42. Meanwhile, the pretest average score obtained by the creative dance creativity variable was 65.21 with a posttest average score of 80.83. The results of the t-test calculation obtained a score of 3.787 greater than the table, namely 2.064 with a significant level of 0.000 <0.05, which means that the results of this study are that there is a difference between before and after treatment. Thus, it can be concluded that there is an influence in the use of digital media on students' creativity abilities through extracurricular dance.